Glutathione and adaptive immune responses against Mycobacterium tuberculosis infection in healthy and HIV infected individuals. - Carlos Guerra (Public Library of Science (PLoS), 2011)
Glutathione (GSH), a tripeptide antioxidant, is essential for cellular homeostasis and plays a vital role in diverse cellular functions. Individuals who are infected with Human immuno deficiency virus (HIV) are known to be susceptible to Mycobacterium tuberculosis (M. tb) infection. We report that by enhancing GSH levels, T-cells are able to inhibit the growth of M. tb inside macrophages. In addition, those GSH-replenished T cell cultures produced increased levels of Interleukin-2 (IL-2), Interleukin-12 (IL-12), and Interferon-gamma (IFN-γ), cytokines, which are known to be crucial for the control of intracellular pathogens. Our study reveals that T lymphocytes that are derived from HIV infected individuals are deficient in GSH, and that this deficiency correlates with decreased levels of Th1 cytokines and enhanced growth of M. tb inside human macrophages.